2017
DOI: 10.3389/fphys.2017.00734
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Subfamilies of Odorant Binding Proteins in Locust (Orthoptera, Acrididae): Molecular Evolution, Structural Variation, and Sensilla-Specific Expression

Abstract: Odorant binding proteins (OBPs) play an important role in insect olfaction, facilitating transportation of odorant molecules in the sensillum lymph. While most of the researches are concentrated on Lepidopteran and Dipteran species, our knowledge about Orthopteran species is still very limited. In this study, we have investigated OBPs of the desert locust Schistocerca gregaria, a representative Orthopteran species. We have identified 14 transcripts from a S. gregaria antennal transcriptome encoding SgreOBPs, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 77 publications
4
40
0
Order By: Relevance
“…The presence of Orco‐positive cells in the palps leads to the question of what types of OBPs may be expressed in sensilla of the palps. In a previous study we identified 14 antennal OBPs of desert locust S. gregaria (Jiang et al , ). Specific primers for each of the 14 OBPs were employed in RT‐PCR experiments to assess cDNA from maxillary and labial palps for OBP expression.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The presence of Orco‐positive cells in the palps leads to the question of what types of OBPs may be expressed in sensilla of the palps. In a previous study we identified 14 antennal OBPs of desert locust S. gregaria (Jiang et al , ). Specific primers for each of the 14 OBPs were employed in RT‐PCR experiments to assess cDNA from maxillary and labial palps for OBP expression.…”
Section: Resultsmentioning
confidence: 99%
“… Overview of the expression of OBPs in either sensilla basiconica and/or sensilla chaetica of the antennae (Jiang et al , ; ) or palps of Schistocerca gregaria . The expression pattern was similar in labial and maxillary palps. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations